Boosting the Redox Kinetics of High‐Voltage P2‐Type Cathode by Radially Oriented 010 Exposed Nanoplates for High‐Power Sodium‐Ion Batteries. Issue 1 (13th January 2022) - Li, Feng; Fan, Ke; Hou, Peiyu; Huang, Haitao
Abstract : Sodium‐Ion Batteries High‐voltage P2‐type cathodes suffer from sluggish reaction kinetics. In article number 2100123 by Peiyu Hou, Haitao Huang, and co‐workers, hierarchically assembled nanoplates with highly exposed 010 facets are designed to achieve high power density sodium‐ion batteries.